Clinical Performance of the EuroSCORE II Compared with the Previous EuroSCORE Iterations - Velicki, Lazar; Cemerlic-Adjic, Nada; Pavlovic, Katica; Mihajlovic, Bojan B.; Bankovic, Dragic; Mihajlovic, Bogoljub; Fabri, Miklos (The Thoracic and Cardiovascular Surgeon, 2014)
Background The European System for Cardiac Operative Risk Evaluation (EuroSCORE) II has been recently introduced as an update to the previous versions. We sought to evaluate the predictive performance of the EuroSCORE II model against the original additive and logistic EuroSCORE models.Patients and Methods The study included 1,247 consecutive patients who underwent cardiac surgery procedures during a 14-month period starting from the beginning of 2012. The original additive and logistic EuroSCORE models were compared with the EuroSCORE II focusing on the accuracy of predicting hospital mortality.Results The overall hospital mortality rate was 3.45%. The discriminative power of the EuroSCORE II was modest and similar to other algorithms (C-statistics 0.754 for additive EuroSCORE; 0.759 for logistic EuroSCORE; and 0.743 for EuroSCORE II). The EuroSCORE II significantly underestimated the all-patient hospital mortality (3.45% observed vs. 2.12% predicted), as well as in the valvular (3.74% observed vs. 2% predicted), and combined surgery cohorts (6.87% observed vs. 3.64% predicted). The predicted EuroSCORE mortality significantly differed from the observed mortality in the third and the fourth quartile of patients stratified according to the EuroSCORE II mortality risk (p < 0.05). The calibration of the EuroSCORE II was generally good for the entire patient population (Hosmer-Lemeshow [HL] p = 0.139), for the valvular surgery subset (HL p = 0.485), and for the combined surgery subset (HL p = 0.639).Conclusion The EuroSCORE II might be considered a solid predictive tool for hospital mortality. Although, the EuroSCORE II employs more sophisticated calculation methods regarding the number and definition of risk factors included, it does not seem to significantly improve the performance of previous iterations.
Keywords: cardiac surgery; risk assessment; EuroSCORE; outcome; mortality; prediction